Crime Free Forum - Husna, Hashim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2009)
25 Oct 2009. A forum aiming at zero crime rate among UMP undergraduates by Human Sciences Club was conducted at WDKU1.